Analysis of the Educational Policy Document in the Kingdom of Saudi Arabia in Light of Global Future Trends in Education - Al-Rzouq, Wardah Ali; Al-Zakari, Hamida Ahmed; Al-Bishr, Fatima Abdullah (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the extent to which the content of the educational policy document in the Kingdom of Saudi Arabia aligns with global future trends in the following areas: (1) equality and equity in educational opportunities, (2) skills for learning for work and sustainable development, (3) professional development of teachers, (4) digital learning, and (5) education funding. The study employed the descriptive-analytical documentary method and relied on designing a content analysis tool for the document, The study results revealed that the criterion of equality and equity in educational opportunities ranked first with 83 items in the document, followed by the criterion of skills for learning for work and sustainable development with 67 items. The professional development of teachers ranked third with 32 items, while digital learning ranked second to last with 16 items. The criterion of education funding ranked last with 13 items in the document. Based on the findings, the researchers recommended developing and updating the educational policy document in the Kingdom in light of global future education trends and knowledge economies to achieve sustainability in education. This includes developing the educational system by effectively and efficiently utilizing all modern contemporary means through information and communication technology (ICT), diversifying funding sources through community partnerships and others, and fostering entrepreneurship, autonomy, and innovation among teachers. The study also suggested future studies on the topic.